Pengaruh pengetahuan, sosialisasi, dan sanksi pajak terhadap kepatuhan wajib pajak orang pribadi di surakarta - Nabila Irsya Khoirunnisa; Yuanita Ayu Marwati; Rhomadani Putriani Devitasari; Rini Handayani (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This study aims to analyze the effect of tax knowledge, tax socialization, and tax sanctions on compliance of individual taxpayers in Surakarta. Methods – This research uses a quantitative approach. The population is individual taxpayers in the Surakarta area. Data collection techniques with conviening sample. Data analysis tools using SPSS version 20. Primary data is generated from distributing questionnaires. Findings - The results showed that knowledge and socialization variables had a positive and significant effect on taxpayer compliance. On the other hand, tax sanctions have a positive, but insignificant effect on compliance. Implications - The findings support the theory of planned behavior which strengthens the research results to further consider effective programs to improve compliance. This research is expected to be a consideration for the government in making policies. Originality - This research has a significant research area and the findings produced can answer the differences in the results of previous studies.